Usefulness of CT angiography in surgery peripheral vascular Preliminary communication of a series on the subject of a case of common carotid artery occlusion - Puñal, Alicia; Kamaid, Emil; Boschi, Jorge; Dutto, Gabriel (Cirugía del Uruguay, 2006)
A patient was suffering from right carotid occ/usion however ultrasound and arteriography showed contradictory results. Angiotomography confirmed occ/usion of primitive carotid and permeability of interna/ carotid, with adequate determination of degree of stricture. A right sube/avían carotid bridge was performed. This paper is a preliminary report of a series evaluating the results of angiotomography in periphera/ vascular pathology